Longarm and the deadly sisters - Evans, Tabor (Evans, Tabor. Longarm, 2014)
Double the beauty, double the trouble, the Olsen sisters, who are responsible for killing a polygamous politician, give Deputy U.S. Marshal Custis Long a run for his money as he tries to bring them to justice.